Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s00464-015-4364-x
|View full text |Cite
|
Sign up to set email alerts
|

The short-term and oncologic outcomes of laparoscopic versus open surgery for T4 colon cancer

Abstract: Our results indicate that laparoscopy is a surgically safe and oncologically acceptable approach and thus could be considered for well-selected patients with T4 colon cancer in order to allow faster short-term recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
62
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 27 publications
(60 reference statements)
8
62
0
2
Order By: Relevance
“…Colon cancer is characterized by various genetic and epigenetic changes (19), as well as molecular alterations. However, further studies are required to identify novel therapeutic targets to develop new treatment strategies (20). In the present study, the expression of miRNA-193b in human patients with CRC was determined to be high, as compared with healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Colon cancer is characterized by various genetic and epigenetic changes (19), as well as molecular alterations. However, further studies are required to identify novel therapeutic targets to develop new treatment strategies (20). In the present study, the expression of miRNA-193b in human patients with CRC was determined to be high, as compared with healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors compared laparoscopic colorectal surgery in older patients with open surgery and substantially suggested that the minimally invasive procedures had a greater benefit on them. Few studies indicated that laparoscopy is a surgically safe and acceptable treatment approach for well-selected patients with colon cancer to ensure faster short-term recovery of the patients [9,16]. Until now, there have been no studies to determine whether minimally invasive surgery affects the ability to retrieve 12+ LNs in elective colon cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found that the mean number of LNs retrieval is greater in open CME [9]. When comparing laparoscopic colectomy and open colectomy, there has been no significant difference in number of LNs resected [9,16], and single-port versus multi-port laparoscopic techniques have also shown no significant difference in terms of number of harvested LNs [13,17].…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations